SELF-REPORTED ANXIETY AND DEPRESSION SYMPTOMS UNDER COVID-19 LOCKDOWN: AN ALBANIAN EXPERIENCE - Akshija, Ilir (JTH: Journal of Technology and Health, 2025)
COVID-19 pandemic, a mostly similar public health issue from country to country represents social, economic and political specific conditions. We attempt through a questionnaire published in the social media Facebook during pandemic lockdown to give a scenery of anxiety and depression symptoms in an Albanian population segment. The questionnaire was constructed following the guidelines of an Islamic sacred text (hadith) known as “five before five”. The sample is considered a virtual snowball sample because some promoters served as seeds making possible to reach parts of the population otherwise impossible to reach making it a sequential experiment ended based on risk of questionnaire misuse. The number or responders (N=1,376) were female 66.6%, age (M=34.9; SD=10.2) and males, age, (M=38.2; SD=10.8). Increase in self-reported anxiety and depression symptoms was common, 851 (61.8%) of responders. Linear logistic regression model shows the relationship of each dimension (health, wealth and free time) to other dimensions’ questions making a presumption to use the present model while retrieving data from other sources for future evaluation of anxiety and depression in a population. For a cut-off value for all dimensions change from baseline of 0.425, Sensitivity (S) was 0.749 and specificity (Sp) was 0.429, raising the problem of missing false negatives with increasing symptoms of anxiety and depression. While television and social media are helpful during a pandemic, the risk of misuse for political and other gains is present too. The citizen in need of recommendations is expected to collaborate but attentive not to abuse his/her trust.